The effect of virtual reality on reducing patients' anxiety and pain during dental implant surgery - Alireza Ghobadi; Hedaiat Moradpoor; Hamid Sharini; Habibolah Khazaie; Pooya Moradpoor (BMC, 2024)
Abstract Background Dental anxiety and pain pose serious problems for both patients and dentists. One of the most stressful and frightening dental procedures for patients is dental implant surgery; that even hearing its name causes them stress. Virtual reality (VR) distraction is an effective intervention used by healthcare professionals to help patients cope with unpleasant procedures. Our aim is to evaluate the use of high-quality VR and natural environments on dental implant patients to determine the effect on reducing pain and anxiety. Methods Seventy-three patients having two dental implant surgeries participated in a randomized controlled trial. One surgery was with VR, and one was without. Anxiety was measured with the the State-Trait Anxiety Inventory and the Modified Dental Anxiety Scale tests. The pain was measured with the Numerical Rating Scales. Patient satisfaction, surgeon distress, memory vividness, and time perception were evaluated. Physiological data were collected with biofeedback and neurofeedback device. Results VR effectively reduced anxiety and pain compared to no VR. Physiological data validated the questionnaire results. Patient satisfaction increased, with 90.4% willing to reuse VR. VR reduced time perception and memory vividness. Conclusion Psychometric and psychophysiological assessments showed that VR successfully reduced patient pain and anxiety. More dental clinicians should use VR technology to manage patient anxiety and pain.